Social Marketing and Corporate Social Responsibility on the Brand Image of Lifebuoy Bath Soap Products - Gogi Kurniawan (Enrichment : Journal of Management, 2022)
The research objective is to determine the effect of Social Marketing and Corporate Social Responsibility on Brand Image. The population of this research is all consumers of Lifebuoy Bath Soap in the last six months. While the research sample used is 30. The data analysis technique used is multiple linear regression analysis to determine the level of disclosure of Social Marketing and Corporate Social Responsibility and Brand Image. The results of the study can be concluded that Social Marketing and Corporate Social Responsibility simultaneously have a significant influence on the Brand Image of Lifebuoy Bath Soap. Partially, the Social Marketing and Corporate Social Responsibility variables are proven to have a significant effect on the Brand Image of Lifebuoy Bath Soap.